Wood-based aerogel with “micro screen” structure: employing multi-layers retention barriers for salt evaporation resistance and lithium adsorption - Mingfeng Dong; He Zhang; Zizheng Zhu; Tao Zhang; Dongya Yang; Fengxian Qiu (Desalination, 2026)

Excavation-induced disturbance analysis of deeply buried tunnels under three-dimensional stress: A numerical investigation - Chaojun Jia; Linyu Liu; Mingfeng Lei; Manchao He; Yingming Xiao (Transportation Geotechnics, 2026)

Self-assembly of phycocyanin-nanochitin complexes for antioxidant Pickering emulsions - Yongqi Tian; Mingfeng He; Xinyi Guo; Yi Yuan; Shaoyun Wang (Food Research International, 2026)

Comprehensive cooling strategy for long-distance blind-heading tunnel construction in tropical plateau regions: a case study - Zhu Peng; Chenghua Shi; Chaojun Jia; Yingzhe Jiang; Hong He; Keyue Zheng; Mingfeng Lei (Tunnelling and Underground Space Technology, 2026)

Metabolic profiling of triptophenolide in rat plasma, urine, bile and faeces after intragastric administration - Mingfeng Jiang; Qiang Hou; Shuilian Wu; Xiaofan He; Tingting Zhang; Rongjing Zhou (Natural Product Research, 2025)

Insight into metal-support interactions of NiMo hydrodesulfurization catalysts and their variations during application - Wenhui He; Yanjuan Xiang; Mudi Xin; Weiming Zhai; Sicong Qiao; Nan Zhang; Limei Qiu; Siyang Yan; Feng Liu; Jianqiang Wang; Guangtong Xu; Jiaxu Liu; et al. (Chemical Engineering Journal, 2025)

Multivariate data analysis of a severe air pollution event in Shihezi city, China - Feifan Chen; Qing He; Zhujun Zhao; Zhongqi Lu; Mingfeng Yang; Gang Ren; Jin Wang; Hongwei Zhang; Dongliang An; Chunxia Wu (Atmospheric Pollution Research, 2025)

Influence of aromatics on the hydrodesulfurization reaction pathway of the NiMo/Al2O3 catalyst using quasi-in situ characterization techniques - Longxin Gao; Wenhui He; Weiming Zhai; Mudi Xin; Wei Wang; Yanjuan Xiang; Hui Yuan; Sa Wang; Feng Liu; Guangtong Xu; Limei Qiu; Mingfeng Li (Fuel, 2025)

Ultrasonic assisted enzymatic extraction, structural characterization, and tyrosinase inhibition mechanism of phlorotannins from Sargassum horneri - Yongqi Tian; Ding Deng; Haitao Luo; Mingfeng He; Shaoyun Wang (Algal Research, 2025)

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

In situ tracking of the impact of atomic-scale fragment structures on MoS2 nanocrystals for high-stability industrial NiMo/γ-Al2O3 hydrodesulfurization catalysts - Wenhui He; Mudi Xin; Yanjuan Xiang; Weiming Zhai; Zheng Chen; Limei Qiu; Aiguo Zheng; Feng Liu; Le Zhang; Guangtong Xu; Mingfeng Li (Chemical Engineering Journal, 2024)

Seasonal pollution and surface characteristics of microplastics in surface water in the Wanzhou section of the Three Gorges Reservoir, China - Ying He; Qian Huang; Qilong Wang; Mingfeng Tang; Xiaoyu Lu; Fei Cheng; Guosheng Xiao (Environmental Science and Pollution Research, 2023)
The pollution of freshwater environments with microplastics (MPs) has attracted increasing attention owing to their threats to aquatic ecosystems and human health. Here, we sampled and analyzed MPs from mainstream, tributary, and backwater areas in the Wanzhou section of the Three Gorges Reservoir (TGR) in impoundment and flood periods. Microplastic pollution was the most severe in the backwater areas. The average abundance of MPs reached the highest value in the flood period (5.27±3.47×10 7 items km −2 ), which was 3–5 times that in the impoundment period. In the 0.3–5 mm size class, the 1–5 mm fraction was the most abundant, accounting for more than 81% in the flood period and 68% of the total MP particle abundance in the impoundment period in the mainstream and backwater areas. However, 0.3–1 mm MPs contributed more than 50% in the tributaries during the impoundment period. Polystyrene, polypropylene, and polyethylene MPs were detected in foam, fragment, sheet, and line-shaped MP particles. White, opaque, foamed polystyrene MPs contributed 32–81% to total MP particle abundance in the watershed. Microplastic particle surfaces showed signs of damage and oxidation, and ten different elements were found. Oxygen was clustered on the surface of foam and fragment MPs. Microplastic pollution was severe in the Wanzhou watershed. Especially in the backwater areas, oxidized MPs of variable shapes derived mainly from surface runoff in the flood period and sewage discharge in the impoundment period were abundant. The results of this study contribute to understanding seasonal pollution patterns and surface characteristics of MPs in the TGR and similar watersheds.

Oceanic vertical mixing of the lower halocline water in the Chukchi Borderland and Mendeleyev Ridge - Long Lin; Hailun He; Yong Cao; Tao Li; Yilin Liu; Mingfeng Wang (Acta Oceanologica Sinica, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Overexpressing fusion proteins of 4-coumaroyl-CoA ligase (4CL) and stilbene synthase (STS) in tobacco plants leading to resveratrol accumulation and improved stress tolerance - Xuancheng He; Feiyan Xue; Lulu Zhang; Huili Guo; Lanqing Ma; Mingfeng Yang (Plant Biotechnology Reports, 2018)

Design, synthesis, and SAR study of highly potent, selective, irreversible covalent JAK3 inhibitors - Linhong He; Mingfeng Shao; Taijin Wang; Tingxuan Lan; Chufeng Zhang; Lijuan Chen (Molecular Diversity, 2018)